ЦІННІСТЬ СПРИЙНЯТТЯ ОСОБИСТОСТІ ЯК АСПЕКТ САМОРЕАЛІЗАЦІЇ В СУЧАСНІЙ КОМУНІКАТИВНІЙ КУЛЬТУРІ - Опанасюк, В. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Розглянуто феномен самореалізації в сучасній комунікативній культурі. Побудовано моделісприйняття особистості в процесі самореалізації. Проаналізовано фактори та механізмсприйняття особистості як цінності на етапі цілепокладання. Опанасюк В.В. Ценность восприятия личности как аспект самореализации всовременной коммуникативной культуре. Рассмотрено феномен самореализации всовременной коммуникативной культуре. Построено модели восприятия личности в процессесамореализации. Проанализировано факторы и механизм восприятия личности как ценности наэтапе целеполагания.Ключевые слова: личность, образ, ценность, самореализация, коммуникативная культура,современная коммуникативная культураValentina V. Opanasyuk. Value of perception of the person as aspect of self-realization inmodern communicative culture. A self-realization phenomenon in modern communicative culture isconsidered. Models of perception of the person in the course of self-realization is constructed. Factorsand the mechanism of perception of the person as values at a purpose formation are analyzed.Keywords: person, image, value, self-realization, communicative culture, modern communicativeculture